(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article examines existing methods for diagnosing polarography in diagnostics. Shown that this method is used in medical laboratories, therapeutic dentistry, express diagnosis of tick-borne encephalitis, as well as to determine the pathology of the maxillofacial area.